Acute management of early post-traumatic epilepsy in patients with mild to moderate traumatic brain injury. (April 2018) - Arai, Takao; Ohta, Shoichi; Tsurukiri, Junya; Oomura, Taishi; Tanaka, Yousuke; Sunaga, Shigeki; Jimbo, Hiroyuki; Ikeda, Yukio; Yukioka, Tetsuo
Background: Continuous electroencephalography (EEG) monitoring for up to 24 h has been suggested to detect non-convulsive epileptic seizures during the acute phase of severe traumatic brain injury (TBI). However, simpler management systems are needed for patients with mild to moderate TBI. Methods: This retrospective single-institution study examined 105 patients admitted for treatment of mild to moderate TBI between 1 June 2012 and 31 March 2016. The study period was 14 consecutive days immediately after TBI. During the acute phase, patients received antiepileptic drug therapy based on physical examination and EEG findings and were subsequently monitored for recurrent or new-onset seizures. Results: In all 105 patients, prophylactic administration of an antiepileptic drug was instituted on hospital admission. Based on physical examination and EEG data obtained during the first 72 h after admission, the patients were divided into three groups: those with (1) epileptiform spikes/waves ( n  = 23), (2) no epileptiform spikes/waves ( n  = 18), and (3) no EEG measurement ( n  = 64). Prophylactic administration of the antiepileptic drug was (1) combined with an adjuvant antiepileptic drug, (2) continued, or (3) discontinued. None of the patients had recurrent or new-onset post-traumatic epilepsy (PTE) or EEG findings indicative of PTE after the combined pharmaceutical intervention during the study period. Conclusion: Our acute management system involving repeated short-duration EEG monitoring allowed for favorable treatment outcomes as no patients developed recurrent or new-onset PTE. This is theoretical grounds for a prospective study of this method to establish a more comprehensive management system with reduced physical and economic burdens on patients.